Controlling parameters for rainfall-induced landslides - Tsaparas, Illias (2011)
Slope instability due to rainfall is a common geotechnical problem in tropical and subtropical areas. The numerical analysis of this problem requires the definition of various hydrological characteristics of the soil in addition to the climatic information. This work attempts to identify the influence of some of those parameters on the stability of an unsaturated soil slope during rainfall. The results of the analysis show that the ratio between the saturated coefficient of permeability with respect to water and the rainfall patterns can significantly influence the seepage pattern within an unsaturated soil slope.